1993
DOI: 10.1002/1097-0142(19931201)72:11+<3416::aid-cncr2820721607>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of intractable cancer pain by electronically controlled parenteral infusion of analgesic drugs

Abstract: Intractable metastatic cancer pain can be controlled in the majority of cases with narcotic drugs. This review focuses on parenteral analgesic therapy; the available drugs, administration systems, and electronic infusion devices. The range of drugs suitable for parenteral therapy, including continuous infusion therapy by subcutaneous, intravenous, or epidural routes is limited both by pharmacokinetic and side effects profiles. Implantable ports and catheter systems permit ambulatory delivery of drugs when comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Many of these systems deliver medications systemically, e.g., as continuous infusion for anesthesia (10) or analgesia (11). A closed-loop feedback system for insulin infusion is in use for diabetes, also with peripheral injection of medication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these systems deliver medications systemically, e.g., as continuous infusion for anesthesia (10) or analgesia (11). A closed-loop feedback system for insulin infusion is in use for diabetes, also with peripheral injection of medication.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical literature on drug delivery systems and use of infusion devices to deliver medications for a variety of human disorders is substantial. Many of these systems deliver medications systemically, e.g., as continuous infusion for anesthesia (10) or analgesia (11). A closed-loop feedback system for insulin infusion is in use for diabetes, also with peripheral injection of medication.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 85 palliative care cancer patients found that the intensity of incident pain may be reduced by increasing the total opioid dose above the prescription required for pain at rest (Mercadante et al , 2004). A major increase in basal dose aimed at reducing incident pain may however result in unacceptable side effects, particularly sedation (Shaw, 1993; Mercadante et al , 2004). The prescription of a CNS stimulant (e.g.…”
Section: Pharmacological Measures To Reduce Pain Perceptionmentioning
confidence: 99%
“…Health care professionals can utilize the therapeutic relationship to assist patients with their ‘human’ response to their cancer and their pain (Taylor, 1988; Thorne et al , 2005; Liu and Fawcett, 2008). The ability of an individual to cope with pain is related to how one perceives the pain, the meaning they attribute to it and the level of fear it invokes (Shaw, 1993; Taylor, 1988; Payne, 2000). A common fear for cancer patients is that of a painful death (Miller and Massie, 2006).…”
Section: Therapeutic Relationshipmentioning
confidence: 99%
“…administration include phlebitis, noscomial infection and cost, for it usually requires hospitalisation, although the development of portable ambulatory infusion pumps has made this technique adaptable to the home health care setting in appropriately selected patients [34].…”
Section: Intravenous Administrationmentioning
confidence: 99%